Decreased CSF Levels of ß-Amyloid in Patients With Cortical Superficial Siderosis - Catak, Cihan; Zedde, Marialuisa; Malik, Rainer; Janowitz, Daniel; Soric, Vivian; Seegerer, Anna; Krebs, Alexander; Düring, Marco; Opherk, Christian; Linn, Jennifer; Wollenweber, Frank A. (Frontiers in Neurology, 2019)
Background: Cortical superficial siderosis (cSS) represents a key neuroimaging marker of cerebral amyloid angiopathy (CAA) that is associated with cognitive impairment. Nevertheless, the mechanisms of cognitive impairment in patients with CAA and cSS remain unclear. Therefore we aimed to analyze core cerebrospinal fluid (CSF) biomarkers for dementia stratified for the presence and extend of cSS. Methods: 101 patients with probable (79%, 80/101) or possible (21%, 21/101) CAA according to the modified Boston criteria and mild cognitive impairment according to Petersen criteria were prospectively included between 2011 and 2016. CSF analyses of ß-amyloid 42, ß-amyloid 40, total tau and phosphorylated tau were performed using sandwich-type enzyme-linked immunosorbent-assay. All patients received MRI and Mini-Mental-State Examination (MMSE). Logistic regression analysis was used to adjust for possible confounders. Results: cSS was present in 61% (62/101). Of those, 53% (33/62) had disseminated cSS and 47% (29/62) focal cSS. ß-amyloid 42 was lower in patients with cSS than in patients without cSS (OR 0.2; 95% CI 0.08-0.6; p=0.0052) and lower in patients with disseminated cSS than in those with focal cSS (OR 0.02; 95% CI 0.003-0.2; p=0.00057). Presence of cSS had no association with regard to ß-amyloid 40, total tau and phosphorylated tau. Conclusions: Our results demonstrate that the presence and extent of cSS are associated with reduced CSF ß-amyloid 42 levels. Further studies are needed to investigate the underlying mechanisms of this association.